The Relevance of 21st Century Education Skills with the Values in the Tarbawi Hadith - Adept Wahyu Wijaya; Ahmad Yusam Thobroni; M Baihaqi (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to analyze the profound relevance between 21st century skills, namely 4C: Critical Thinking, Communication, Collaboration, Creativity, with the values of the Tarbawi hadith and to formulate an integrative education model. The research used a qualitative approach with library research method through content analysis of 21st century skills literature and the value of Tarbawi hadith. The findings reveal a fundamental and operational alignment between the two frameworks: critical thinking aligns with the concepts of tafaqquh, tadabbur, and tafakkur; communication aligns with the ethics of qaulan sadida, karima, and layyinan; collaboration aligns with the spirit of ta’awun and ukhuwah; and creativity aligns with the tradition of ijtihad and is oriented toward ishlah. This study concludes that the integration of 21st century skills and Hadith Tarbawi values is essential for creating holistic education. The implication is that educators and curriculum developers need to design learning models that organically unite the achievement of 21st century competencies with the internalization of Islamic values, in order to realize the Golden Generation of 2045 that is both competent and of noble character.